2016
DOI: 10.1164/rccm.201504-0782oc
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Antiviral Function of CD8+T Cells in the Chronic Obstructive Pulmonary Disease Lung. Role of the PD-1–PD-L1 Axis

Abstract: Rationale: Patients with chronic obstructive pulmonary disease (COPD) are susceptible to respiratory viral infections that cause exacerbations. The mechanisms underlying this susceptibility are not understood. Effectors of the adaptive immune response-CD8 1 T cells that clear viral infections-are present in increased numbers in the lungs of patients with COPD, but they fail to protect against infection and may contribute to the immunopathology of the disease. Objectives: CD81 function and signaling through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 38 publications
(46 reference statements)
5
127
0
Order By: Relevance
“…As an important regulator of T-lymphocyte function which is associated with a loss of cytotoxic function, the upregulation of PD-1 in T lymphocytes reduces CD8+ T-cell function in response to influenza. Specifically, this was associated with diminished T-cell cytotoxic degranulation in response to viral infection, supporting the concept of diminished T-lymphocyte response to viral infection in patients with COPD [McKendry et al 2015].…”
Section: Copd and The Immune Systemsupporting
confidence: 58%
“…As an important regulator of T-lymphocyte function which is associated with a loss of cytotoxic function, the upregulation of PD-1 in T lymphocytes reduces CD8+ T-cell function in response to influenza. Specifically, this was associated with diminished T-cell cytotoxic degranulation in response to viral infection, supporting the concept of diminished T-lymphocyte response to viral infection in patients with COPD [McKendry et al 2015].…”
Section: Copd and The Immune Systemsupporting
confidence: 58%
“…We thank Dr Stoll and colleagues for highlighting the clinically important issues raised by the recent work on the PD1 axis in COPD (1,2). In light of these findings we share their concern that the use of anti-PD-1-PD-L1 therapies in patients with non-small cell lung cancer (NSCLC) and COPD may have unwanted effects on the underlying airway inflammatory process.…”
Section: To the Editormentioning
confidence: 89%
“…recently showed that upon ex vivo infection of resected lung tissue with influenza A virus, there was significantly greater IFN‐ γ production by explants from patients with COPD than from healthy controls,49 suggesting that inadequate IFN‐ γ production is not the cause of pathological inflammation in viral infections in patients with COPD 49…”
Section: Discussionmentioning
confidence: 99%